2011
DOI: 10.5194/acp-11-11455-2011
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol optical properties and radiative effect determined from sky-radiometer over Loess Plateau of Northwest China

Abstract: Abstract. The aerosol optical properties and their associated radiative effects are derived from sky-radiometer and surface solar radiation data collected over the Semi-Arid Climate and Environment Observatory of Lanzhou University (SACOL) for the period of March to May (MAM) 2009. The result shows that the seasonal mean aerosol optical depth (AOD) at 500 nm in MAM is 0.40. The single scattering albedo (SSA) at 500 nm in MAM at SACOL fluctuates significantly ranging from 0.82 to 0.98. The averaged value of SSA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(63 citation statements)
references
References 37 publications
3
53
0
1
Order By: Relevance
“…Guan et al (2015a) found that the enhanced warming in drylands was a result of radiativeforced temperature, which has a close relationship with aerosol column burden. The aerosol in drylands has an obvious warming effect (Huang et al, 2006aChen et al, 2010;Ye et al, 2012;Jin et al, 2015), and the aerosol has a wide distribution and tends to have a relatively large optical depth (H. Bi et al, 2011;Liu et al, 2011;, leading to a significant radiative effect in the drylands. According to the results of Tegen and Fung (1995), the existing atmospheric dust load is hard to explain by natural sources alone.…”
Section: Introductionmentioning
confidence: 99%
“…Guan et al (2015a) found that the enhanced warming in drylands was a result of radiativeforced temperature, which has a close relationship with aerosol column burden. The aerosol in drylands has an obvious warming effect (Huang et al, 2006aChen et al, 2010;Ye et al, 2012;Jin et al, 2015), and the aerosol has a wide distribution and tends to have a relatively large optical depth (H. Bi et al, 2011;Liu et al, 2011;, leading to a significant radiative effect in the drylands. According to the results of Tegen and Fung (1995), the existing atmospheric dust load is hard to explain by natural sources alone.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [34] found the decrease of residual aerosol and an unusual case of residual aerosol increase during the different processes of a haze episode. In addition, some research concentrated on the properties of a single type aerosol, e.g., urban-industrial (e.g., [40]), rural (e.g., [32]), desert dust (e.g., [41]), and oceanic [42].…”
Section: Introductionmentioning
confidence: 99%
“…Values of α greater than 1.6 and α values less than 0.8 accounted respectively for 1.3% and 8.2% of the total. It is reported that the probability distribution of α has a modal value of 1.1 and varies in the range 0 to 1.7 over Loess Plateau of Northwestern China (Bi et al, 2011); values of α greater than 1.8 and less than 0.6 accounted respectively, for 0.3% and 1%, over Shanghai, China (He et al, 2012). Meanwhile, the frequency histogram of WVC shows a maximum around 0.6 cm; 75% lower than 2 cm and 64% in the range 0.3-1.8 cm (Fig.…”
Section: Aerosol Optical Depth åNgström Exponent and Water Vapormentioning
confidence: 99%
“…The single scattering albedo (SSA) is a common measurement of the relative contribution of scattering to extinction, which is mostly dependent on the chemical composition, matter concentration and size distribution of (Dubovik et al, 2002;Liu et al, 2011). 08.…”
Section: Single Scattering Albedomentioning
confidence: 99%